Search cost and rural producers' trading choice between middlemen and consumers in Bangladesh - Chowdhury, Shyamal (Mohr Siebeck, 2004)
This paper assesses the impact of search cost - as proxied by the cost of access to telephones - on small-scale producers' choice between trading with middlemen and trading directly with consumers. The empirical findings suggest that search cost plays a significant role in this choice and that a reduction in search cost increases the likelihood of trading with consumers. This result has important implications related to the provision of public telephones in rural areas of developing countries. -- Author's Abstract